Estimation and Determinant Factors of Cocoa Production Efficiency in Indonesia: A Case Study of the Central Sulawesi - EFFENDY, EFFENDY; ANTARA, Made; TANGKESALU, Dance; CHRISTOPORUS, CHRISTOPORUS; PRATAMA, M. Fardhal; LAKSMAYANI, Made Krisna; SULMI, SULMI; BASIR-CYIO, Muhammad; MAHFUDZ, MAHFUDZ; ZAINUDDIN, ZAINUDDIN; MUHARDI, MUHARDI (Journal of Advanced Research in Law and Economics, 2019)
This research aimed to estimate the technical efficiency – allocative and economic – of cocoa farming. The research was conducted in Sigi and Parigi Moutong Regency of Central Sulawesi Province of Indonesia. The data were collected from 282 cocoa farmers in the research area. The results of the research showed that there was a large variation between technical efficiency levels. There was also a large variation between the efficiency level of allocative and economic in cocoa farming, which implied an opportunity to improve cocoa yields at the level of farmers. We concluded that education of farmer, age of farmer, extension visit, farming scale, and age of cocoa crop was the determinant factors of cocoa production efficiency. We suggested that education of farmer, extension access, and age of crop needed to be a priority of the government, as there was sufficient potential to improve cocoa yields in the research area.